Prognostic importance of plasma total magnesium in a cohort of cats with azotemic chronic kidney disease. (27th April 2018) - van den Broek, D. Hendrik N.; Chang, Yu‐Mei; Elliott, Jonathan; Jepson, Rosanne E.
Abstract : Background: Hypomagnesemia is associated with increased mortality and renal function decline in humans with chronic kidney disease (CKD). Magnesium is furthermore inversely associated with fibroblast growth factor 23 (FGF23), an important prognostic factor in CKD in cats. However, the prognostic significance of plasma magnesium in cats with CKD is unknown. Objectives: To explore associations of plasma total magnesium concentration (tMg) with plasma FGF23 concentration, all‐cause mortality, and disease progression in cats with azotemic CKD. Animals: Records of 174 client‐owned cats with IRIS stage 2‐4 CKD. Methods: Cohort study. Cats with azotemic CKD were identified from the records of two London‐based first opinion practices (1999–2013). Possible associations of baseline plasma tMg with FGF23 concentration and risks of death and progression were explored using, respectively, linear, Cox, and logistic regression. Results: Plasma tMg (reference interval, 1.73–2.57 mg/dL) was inversely associated with plasma FGF23 when controlling for plasma creatinine and phosphate concentrations (partial correlation coefficient, −0.50; P  < .001). Hypomagnesemia was observed in 12% (20/174) of cats, and independently associated with increased risk of death (adjusted hazard ratio, 2.74; 95% confidence interval [CI], 1.35–5.55; P  = .005). The unadjusted associations of hypermagnesemia (prevalence, 6%; 11/174 cats) with survival (hazard ratio, 2.88; 95% CI, 1.54–5.38; P  = .001), and hypomagnesemia with progressive CKD (odds ratio, 17.7; 95% CI, 2.04–154; P  = .009) lost significance in multivariable analysis. Conclusions and Clinical Importance: Hypomagnesemia was associated with higher plasma FGF23 concentrations and increased risk of death. Measurement of plasma tMg augments prognostic information in cats with CKD, but whether these observations are associations or causations warrants further investigation.